(untitled) (CIPEEX, 2025)
Kinesio Taping has emerged as a complementary therapeutic resource in both postpartum recovery and postoperative rehabilitation. Its proposed effects include improvement of lymphatic drainage, reduction of edema, pain control, and support of musculoskeletal structures, contributing to functional recovery and patient well-being. This narrative review aims to analyze the evidence regarding the use of Kinesio Taping in postpartum women and patients in the postoperative period, focusing on its mechanisms of action, clinical applications, and reported benefits. Articles published in PubMed, Scielo, and ScienceDirect were reviewed to provide a comprehensive overview of the subject. The findings suggest that taping is effective in reducing swelling and discomfort, improving circulation, enhancing tissue healing, and supporting abdominal and musculoskeletal stability in postpartum recovery. In postoperative care, its application has been associated with decreased pain, accelerated functional return, and prevention of complications such as seroma and hematoma. Despite its promising results, current literature still highlights the need for standardized protocols and further randomized clinical trials to confirm efficacy and long-term outcomes. In conclusion, Kinesio Taping represents a safe, low-cost, and non-invasive therapeutic tool that can be incorporated into multidisciplinary strategies for postpartum and postoperative management.